Team Reasoning as a Guide to Coordination - Amrei M. Lahno; Bernd Lahno (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
A particular problem of traditional Rational Choice Theory is that it cannot explain equilibrium selection in simple coordination games. In this paper we analyze and discuss the solution concept for common coordination problems as incorporated in the theory of Team Reasoning (TR). Special consideration is given to TR's concept of opportunistic choice and to the resulting restrictions in using private information. We report results from a laboratory experiment in which teams were given a chance to coordinate on a particular pattern of behavior in a sequence of HiLo games. A modification of the stage game offered opportunities to improve on the team goal through changing this accustomed pattern of behavior. Our observations throw considerable doubt on the idea of opportunistic team reasoning as a guide to coordination. Contrary to what TR would predict, individuals tend to stick to accustomed behavioral patterns. Moreover, we find that individual decisions are at least partly determined by private information not accessible to all members of a team. Alternative theories of choice, in particular cognitive hierarchy theory may be more suitable to explain the observed pattern of behavior.
urn:nbn:de:bvb:19-epub-20822-4
Keywords: C91; C92; D03; D70; 330; team reasoning; collective agency; coordination; opportunistic choice; laboratory experiment